2021
DOI: 10.1177/00953997211028825
|View full text |Cite
|
Sign up to set email alerts
|

Theorizing Status Distance: Rethinking the Micro Theories of Representation and Diversity in Public Organizations

Abstract: Through bringing the concept of status distance to representative bureaucracy and diversity management literature, this article develops new hypotheses that can guide future studies on representation and diversity in public organizations. First, including status distance brings consideration of the tensions that minority representation creates between integration within the workforce and the pressures on minority bureaucrats to actively represent clientele. Second, the way status distance plays out in the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 74 publications
0
24
0
Order By: Relevance
“…Yet, questions arise whether the effect of passive representation is limited to individual minorities or could be expanded to, most notably, nonminority members within an organization and/or the society. Recent studies present several pathways that involve an impact on nonminority bureaucrats and minority clientele (Favero and Molina Jr 2018; Groeneveld et al 2015; Groeneveld and Meier 2021; Guul 2018; Vinopal 2018). The effect of bureaucratic representation may also depend on the intraorganizational interaction between minority bureaucrats and their nonminority colleagues within the bureaucracy, and the effect may increase as the relationship becomes highly interactive (Groeneveld and Meier 2021).…”
Section: Theory and Literaturementioning
confidence: 99%
See 4 more Smart Citations
“…Yet, questions arise whether the effect of passive representation is limited to individual minorities or could be expanded to, most notably, nonminority members within an organization and/or the society. Recent studies present several pathways that involve an impact on nonminority bureaucrats and minority clientele (Favero and Molina Jr 2018; Groeneveld et al 2015; Groeneveld and Meier 2021; Guul 2018; Vinopal 2018). The effect of bureaucratic representation may also depend on the intraorganizational interaction between minority bureaucrats and their nonminority colleagues within the bureaucracy, and the effect may increase as the relationship becomes highly interactive (Groeneveld and Meier 2021).…”
Section: Theory and Literaturementioning
confidence: 99%
“…A recent meta‐analysis indicated that street‐level bureaucrats with expertise and discretion have a greater impact on citizens/clients and bureaucratic performance (Ding, Lu, and Riccucci 2021). However, only a few studies have examined both the supervisory‐level and street‐level representation within a bureaucratic organization (e.g., Agyapong 2018; Keiser et al 2002; Meier and Stewart Jr 1992; Wilkins and Keiser 2006, among others), and demographic congruence between supervisors (managers) and subordinates (frontline bureaucrats) (e.g., Grissom and Keiser 2011; Grissom, Nicholson‐Crotty, and Keiser 2012; Groeneveld and Meier 2021).…”
Section: Theory and Literaturementioning
confidence: 99%
See 3 more Smart Citations